Digital current sensing in modular multilevel converter for HVDC applications - A. Yahaya, J.; Mansor, Muhamad; Hadi, Abdul (Medwell Publications, 2017)
For long-distance transmission, HVDC (High-Voltage, Direct-Current) is proven to be less expensive and have lower electrical losses as compared to HVAC (High-Voltage, Alternating-Current). Now a days, the advancement of power electronic switches such as IGBT's and MOSFET enables the use of converters for HVDC applications. Among the well-known converters used for HVDC are Voltage Source Converter (VSC) Line Commutated Converter (LCC) and Modular Multilevel Converter (MMC). The MMC is still new and a promising technology for HVDC application. The MMC has many advantages such as controlling high amount of active/reactive power and possess lower losses as compared to other converters. To control the active/reactive power in a MMC, control scheme such as free-running hysteresis uses the reference voltage and the inductor current to produce the required switching pulses. This study proposed a technique in which a voltage sensor is use to measure the inductor current. Conventionally, the inductor current is sensed either with a resistor or Current Transformer (CT). This method is associated with some disadvantages; requires additional circuitry which introduces some power loss and requires higher bandwidth in order to sense accurately. This study instead, measures the current indirectly by using the information of the phase inductor voltage. As the voltage sensor is placed in parallel to the inductor, this measuring technique is immune to I2R loss. The proposed technique will be investigated using MATLAB simulation to determine its current sensing capability in a MMC for HVDC applications. To design an improved current-less sensing method using a digital RC network. To extract the inductor current values from the phase inductor voltage an RC filter is required and placed in parallel across the inductor. In this way, all the high frequency harmonics will be filtered out and only the low frequency inductor current can be seen across the capacitor. The selection of RC values, however is dependent on the inductor value and inductor DC-Resistance (RDCR). The main concern with this technique is that selection of DCR RC values sometimes can be unavailable for hardware implementation. To further improve the implementation of RC network and eliminate the problems of selecting suitable RC values for hardware implementation. This paper proposed the used of digital filter based on the RC network concept. Instead of using the actual components for filtering the high frequency harmonics, this technique uses only the DSP for filtering to remove the high frequency harmonics. The proposed technique is able to convert the high frequency voltage VL1 measured from the phase inductor L1 into the phase inductor current iL1without any delay or difficulty. By 1 L1 comparing the signals of proposed method to the series sensing method and the conventional RC filter method the waveforms of both signals are almost identical. However, the proposed method eliminates the need for RC components as compared to the conventional RC filter method. This technique improves the efficiency of the system in terms of improve signal noise ratio and eliminates the need for passive component on the system.